Africa and foreign aid for development: a reflection from the perspective of global ethics - Carreño, Eduardo A. (Acta Bioethica, 2013)
After World War II it was suggested that in order to reduce poverty it was needed economic modernization, that is, less developed countries should follow the path of the industrialized countries, for which only it was required aid to allow evolution and prosperity around the world. However, this paradigm was questioned after the end of Cold War, particularly when evaluating the impact on Africa of foreign aid for development. In this sense, the aims of this paper are to analyze how the international system has determined the political and economic strategies of African countries; to address the ethical debate raised on foreign aid for development; and to estimate the impact in African strategies to overcome poverty.